URGENSI PERLINDUNGAN HUKUM TERHADAP ANAK DI KABUPATEN ACEH BARAT DAYA - Sri Wahyuni; Nila Trisna (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2023)
This study aims to analyze and examine the urgency of legal protection for children in Aceh Barat Daya district. Violence against children, sexual abuse of children, trafficking of children to be exploited as commercial sex workers, neglect of children, and killing of children are still common. This can prove that child protection in Indonesia is still very weak so that it must receive special attention from both the state, government, local government, parents, families and the community around the child. The large number of criminal cases against children in Aceh Barat Daya district indicates that the application of legal protection for children is still very weak, thus legal protection for children in Aceh Barat Daya district is an urgent matter. The method used in analyzing and reviewing is research on normative juridical law, namely research whose object is normative law in the form of legal principles and the legal system, in which this research describes the urgency of legal protection for children in Aceh Barat Daya district. The number of cases of criminal acts against children that occurred in Southwest Aceh district adds to the black list of poor legal protection for children in Indonesia. Therefore the protection of children in Aceh Barat Daya district is an urgent matter.